The Use of Synthetic Herbivory-Induced Plant Volatiles That Attract Specialist Parasitoid Wasps, Cotesia vestalis, for Controlling the Incidence of Diamondback Moth Larvae in Open Agricultural Fields - Uefune, Masayoshi; Yoneya, Kinuyo; Yamamoto, Masaki; Takabayashi, Junji (Frontiers in Ecology and Evolution, 2021)
We evaluated the effectiveness of using a blend of volatiles that attract Cotesia vestalis, a specialist parasitoid wasp of diamondback moth (DBM) larvae, to control DBM larvae on cabbage plants under open field conditions. We set three dispensers of the synthetic C. vestalis attractant together with one sugary-food feeder in a cabbage plot (10 m × 1 m; the treated plot) on one side of a pesticide-free open agricultural field (approximately 20 m × 20 m) from June to September in 2010, and July to August in 2011. On the other side of the field, we created a control cabbage plot of the same size in which neither dispensers nor a feeder were set. The incidences of DBM larvae and C. vestalis cocoons in the control and treated plots were compared. Poisson regression analyses of the number of DBM larvae and C. vestalis cocoons were also conducted. In 2010, the incidence of DBM larvae in the treated plot was significantly lower than that in the control plot. Poisson regression analyses in 2010 showed that the rate of increase in the number of C. vestalis cocoons along with an increase in the number of DBM larvae in the treated plot was significantly higher than that in the control plot. In 2011, the incidence in both the treated and control plots remained low (5 larvae per plant or less), with no significant difference between the plots. Poisson regression analyses in 2011 showed that the number of C. vestalis cocoons in the treated plot was significantly higher than that in the control plot, irrespective of the number of DBM larvae. The incidence of Pieris rapae larvae and Plusiinae spp. was not affected by the treatments. The number of aphids in the treated and control plots was inconsistent between the two years. Based on these two-year results, the possible use of C. vestalis attractants in open agricultural fields is discussed.